2010
DOI: 10.1177/1933719110369183
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen-G (HLA-G) Expression in Cervical Lesions: Association With Cancer Progression, HPV 16/18 Infection, and Host Immune Response

Abstract: Human leukocyte antigen-G (HLA-G) expression in 55 cervical intraepithelial neoplasia (CIN) patients with or without human papillomavirus (HPV) infection and 116 patients with squamous cell cervical cancer were examined using immunohistochemistry. Host immune response was assessed by estimating the number of intratumoral lymphocyte infiltration (TIL) in all lesions and counting CD57-expressing cells in the neoplasm lesions. The means of HLA-G immunoreactive scores were compared by the Mann-Whitney test and 1-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 28 publications
(46 reference statements)
3
54
0
Order By: Relevance
“…18 Several studies have demonstrated that cervical cancer tissue expressed HLA-G and that its expression correlates with tumor progression. [5][6][7][8]10 In this report, the wildtype HLA-G*01:01:01 allele conferred protection against invasive cancer, whereas variant HLA-G*01:01:02, -G*01:06 and -G*3 0 UTR 14-bp insertion alleles increased cervical cancer risk. The HLA-G*01:01:02 and -G*01:06 alleles both have a synonymous substitution (Proline) at codon 57.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…18 Several studies have demonstrated that cervical cancer tissue expressed HLA-G and that its expression correlates with tumor progression. [5][6][7][8]10 In this report, the wildtype HLA-G*01:01:01 allele conferred protection against invasive cancer, whereas variant HLA-G*01:01:02, -G*01:06 and -G*3 0 UTR 14-bp insertion alleles increased cervical cancer risk. The HLA-G*01:01:02 and -G*01:06 alleles both have a synonymous substitution (Proline) at codon 57.…”
Section: Discussionmentioning
confidence: 52%
“…3,4 However, the link between HLA-G and cervical cancer has been inconsistent and contradictory in the published reports. For instance, HLA-G expression in cervical cancer tissue has been found to be increased, [5][6][7] reduced, 8 or absent. 9,10 HLA-G expression has correlated positively, 6,7 negatively, 5,10 or not at all 11 with cervical disease progression.…”
mentioning
confidence: 99%
“…High HLA-G mRNA expression may be correlated with early carcinogenesis, since it was associated with early-stage cervical cancer (45). It was demonstrated that HLA-G expression was progressively higher in patients with CIN 1 to CIN 2/3 and was the highest in patients with cervical cancer, suggesting that HLA-G expression in cervical lesions may be associated with carcinogenesis, HPV infection and host immune response (51).…”
Section: Il-10 Exerts a Tumor-promoting Effect In Cervical Cancermentioning
confidence: 93%
“…For example, IL-10 can contribute by increasing HLA-G expression on HLA class Ideficient cells to escape from NK-mediated lysis through interactions with killer inhibitory receptors on NK cells [48,49]. In CeCa lesions, the expression of both HLA-G and IL-10 associated with HPV infection might play an important role in CeCa progression [50,51]. In fact, it has been recently reported that in tissue samples from biopsies derived from patients with CeCa and with loss or downregulation of HLA class I expression, most of the HLA-G-positive cases (87.5%) exhibited upregulation of the IL-10 [52].…”
mentioning
confidence: 99%